Alpheus lentiginosus Anker & Nizinski, 2011, n. sp. ... - Anker, Arthur; Nizinski, Martha (Zenodo, 2011)
Alpheus lentiginosus n. sp. (Figs. 1–3) Type material. Holotype: male (CL 7.9 mm), USNM 1145505, North Atlantic Ocean, Gulf of Mexico, 188.8 km south of Louisiana, expedition USGS DISCOVRE GOM, cruise JSLII-09- GOM, vessel Seward Johnson – DSR/V Johnson Sea Link II, Sta. JSL 3726, 28°11’41”N 89°47’59”W (28.1947250, -89.7999167), Lease Block MC751, Bucket 1, depth 434–438 m, patch reef on soft bottom, base of Lophelia pertusa, S.W. Ross et al., 19 September 2009. Paratype: female (CL 10.1 mm), USNM 1145818, North Atlantic Ocean, Gulf of Mexico, 261.82 km south of Louisiana, expedition USGS-GOM-Lophelia I, cruise USGS-GOM, vessel Seward Johnson – DSR/V Johnson Sea Link I, Sta. JSL 4745, 29°05’53”N 88°23’06”W (29.0979533, -88.3849800), Lease Block VK906/862, Bucket 11, depth 336 m, K. Sulak et al., 30 July 2004. Description. Body moderately slender, laterally not compressed. Carapace glabrous, without marked sculpture; frontal margin with well-developed rostrum and orbital teeth; rostrum subtriangular, distally ... : Published as part of Anker, Arthur & Nizinski, Martha, 2011, Description of a new deep-water species of Alpheus Fabricius, 1798 from the Gulf of Mexico (Crustacea, Decapoda, Alpheidae), pp. 49-56 in Zootaxa 2925 on pages 50-55, DOI: 10.5281/zenodo.201972 ...